Longitudinal Analysis of Neutralizing Potency against SARS-CoV-2 in the Recovered Patients after Treatment with or without Favipiravir - Shinada, Kanako; Sato, Takashi; Moriyama, Saya; Adachi, Yu; Shinoda, Masahiro; Ota, Shinichiro; Morikawa, Miwa; Mineshita, Masamichi; Matsumura, Takayuki; Takahashi, Yoshimasa; Shinkai, Masaharu (Viruses, 2022)
The effect of treatment with favipiravir, an antiviral purine nucleoside analog, for coronavirus disease 2019 (COVID-19) on the production and duration of neutralizing antibodies for SARS-CoV-2 was explored. There were 17 age-, gender-, and body mass index-matched pairs of favipiravir treated versus control selected from a total of 99 patients recovered from moderate COVID-19. These subjects participated in the longitudinal (>6 months) analysis of (i) SARS-CoV-2 spike protein’s receptor-binding domain IgG, (ii) virus neutralization assay using authentic virus, and (iii) neutralization potency against original (WT) SARS-CoV-2 and cross-neutralization against B.1.351 (beta) variant carrying triple mutations of K417N, E484K, and N501Y. The results demonstrate that the use of favipiravir: (1) significantly accelerated the elimination of SARS-CoV-2 in the case vs. control groups (p = 0.027), (2) preserved the generation and persistence of neutralizing antibodies in the host, and (3) did not interfere the maturation of neutralizing potency of anti-SARS-CoV-2 and neutralizing breadth against SARS-CoV-2 variants. In conclusion, treatment of COVID-19 with favipiravir accelerates viral clearance and does not interfere the generation or maturation of neutralizing potency against both WT SARS-CoV-2 and its variants.